Separation and Determination of Paraquat and Diquat in Human Plasma and Urine by Magnetic Dispersive Solid Phase Extraction Coupled with High-Performance Liquid Chromatography - Ou Sha; Bowen Cui; Xiaobing Chen; Hua Liu; Jiawei Yao; Yuqing Zhu (Journal of Analytical Methods in Chemistry)
A magnetic dispersive solid phase extraction method coupled with high-performance liquid chromatography was proposed for the simultaneous separation and determination of paraquat (PQ) and diquat (DQ) in human plasma and urine samples. Based on the reduction of PQ and DQ to a blue radical and yellow-green radical by sodium dithionite in an alkaline medium, a fast colorimetric method was also developed for the fast detection of PQ or DQ. In this paper, CoFe2O4@SiO2 magnetic nanoparticles were used as the adsorbent for the magnetic dispersive solid phase extraction of paraquat and diquat, and these two analytes were found to be eluted directly from the adsorbent by NaOH solution. The main factors affecting the extraction efficiency including amount of extractant, extraction time, sample volume, sample solution pH, and elution volume were optimized. Under the optimized experimental conditions, the calibration curve was linear at a concentration range of 28.5–570.2 μg/L, and the correlation coefficient of paraquat and diquat was 0.9986 and 0.9980, respectively. The limits of detection of paraquat and diquat were 4.5 μg/L and 4.3 μg/L. The proposed MSPE-HPLC method was successfully applied to the detection of the paraquat and diquat in human plasma and urine with satisfied recoveries of PQ and DQ in the range of 87.5%–98.7%.